Analysis of the Relationship between Islamic Religious Education and its Function in Forming Emotional Intelligence in Early Age Children - Yahya Mohammed Abu Bakr; Norakyairee Mohd Raus; Ahmed H. Ibrahim; Atta Ullah Faizi (Al Husna: Jurnal Ilmiah Pendidikan Agama Islam, 2024)
This research aims to analyze the relationship between Islamic Religious Education (PAI) and its function in forming emotional intelligence in early childhood. Emotional intelligence is an important aspect in child development which includes the ability to recognize, understand and manage emotions in oneself and others. Islamic religious education, through teaching moral and spiritual values, is expected to play a significant role in developing children's emotional intelligence. This research uses a qualitative approach with a case study method, involving observation, interviews with teachers and parents, as well as analysis of PAI teaching materials. The research results show that the integration of religious values in the PAI curriculum, such as empathy, patience and cooperation, effectively helps children develop their emotional intelligence. Apart from that, the religious practices taught in PAI, such as praying and reciting the Koran, also have a positive impact on children's emotional management. However, there are challenges in implementing this education, including a lack of training for teachers and limited resources. Therefore, it is recommended to strengthen teacher training and provide adequate resources to support the effective implementation of PAI. Thus, PAI can contribute more to forming the emotional intelligence of young children